Relationships between socio-emotional skills and stress, anxiety and depression disorders in education professionals in the COVID-19 pandemic - Adrião, Silvia; Reichert, Richard Alecsander; Simoes, Amanda; Machado, Tayssa; Micheli, Denise De (Seven Editora, 2023)
The COVID-19 pandemic has generated several challenges worldwide in different spheres of society, including education. This study examined the effects of the COVID-19 pandemic on teaching routine, its associated stress, anxiety, and depression disorders, and how educators’ social-emotional skills are related to these disorders. The main hypothesis was that social-emotional skills have a significant protective effect on psychological problems, suggesting that they should be developed to reduce the prevalence of these disorders. Method: An online survey was conducted through a questionnaire sent to educators of Basic Education and Higher Education from all over Brazil. Results: Based on data from 231 education professionals, it was found that most participants had mild to moderate levels of stress, extremely severe levels of anxiety, and normal levels of depression. Participating teachers reported an abrupt and intense change in work routine during quarantine, but also demonstrated elevated levels of positive thinking, emotional self-control, ability to cope with stress, collaboration, openness to the new and another, and good self-management. It was also found that the more social-emotional skills, the lower the total rates of disorders. Conclusion: The results suggest that social-emotional skills were important factors for better coping with the pandemic, but that health and well-being involve other elements in addition to skills. It is expected that these findings can support intervention strategies aimed at professionals in the field of education. DOI:https://doi.org/10.56238/emerrelcovid19-012